Quality of life and communitarian participation: Psychosocial evaluation of urban upgrading projects in slums - Hernández-Ponce, Luis E.; Reimel de Carrasquel, Sharon (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In order to determine if Quality of Life is a property of people, environment or of relationship between both, a total of 314 heads-of-family were surveyed in three Caracas’s slums with urban upgrading projects. A model based on psychosocial theories, was adapted and updated with the purpose of measuring and evaluating perceived Quality of Life. Statistical analyses showed that personal factors have greater weight in the mesosystem’s physical-material level, whereas environmental factors prevail in the microsystems appraisal, and in the rest of mesosystem’s levels. In conclusion, perceived Quality of Life is a person-environment relationship’s property. The organized communitarian participation stood out as the most important factor in this relationship.